Addressing required changes in the UK health system for the health and wellbeing for individuals with learning (intellectual) disabilities - Northway, Ruth (Henry Stewart Talks, 2020)
Current barriers to healthcare experienced by people with learning disabilities, Difficulties in treating individuals with learning disabilities, How to improve access to healthcare, Improving teaching and training for health service providers